Rail Vehicle Dynamics - Knothe, Klaus; Stichel, Sebastian; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book on the dynamics of rail vehicles is developed from the manuscripts for a class with the same name at TU Berlin. It is directed mainly to master students with pre-knowledge in mathematics and mechanics and engineers that want to learn more. The important phenomena of the running behaviour of rail vehicles are derived and explained. Also recent research results and experience from the operation of rail vehicles are included. One focus is the description of the complex wheel-rail contact phenomena that are essential to understand the concept of running stability and curving. A reader should in the end be able to understand the background of simulation tools that are used by the railway industry and universities today.
Introduction -- Modeling of vehicle, track and excitation -- Modeling of wheel/rail contact -- Vertical dynamics, equations of motion and free vibrations -- Forced vertical vibrations and frequency domain solution -- Random vibrations -- Human perception of vibrations: ride comfort -- Introduction to lateral dynamics -- Equations of motion for lateral dynamics -- Lateral eigenbehavior of a wheelset -- Lateral eigenbehavior and stability of bogies -- Stability of bogie vehicles -- Non-linear stability investigations -- Quasi-static curving behavior. - Load collectives for vehicle components -- Appendix. .
Keywords: Multibody systems; Vibration; Mechanics, Applied; Mechanical engineering; Civil engineering; Transportation engineering; Traffic engineering; Multibody Systems and Mechanical Vibrations; Mechanical Engineering; Civil Engineering; Transportation Technology and Traffic Engineering